ChemInform Abstract: Development of Ceria‐Supported Ruthenium Catalysts for Green Organic Transformation Processes. Issue 19 (18th April 2013) - Wada, Kenji; Miura, Hiroki; Hosokawa, Saburo; Inoue, Masashi
Abstract Review: 82 refs.